478 lines
18 KiB
TeX
478 lines
18 KiB
TeX
\documentclass[../../script.tex]{subfiles}
|
|
% !TEX root = ../../script.tex
|
|
|
|
\begin{document}
|
|
\section{Differential Calculus}
|
|
|
|
\begin{defi}
|
|
Let $I$ be an open interval ($(a, b)$, $a < b$, $a, b = \infty$ possible). Let $f: I \rightarrow \field$ and $x \in I$.
|
|
$f$ is called differentiable in $x$ if
|
|
\[
|
|
f'(x) = \limes{h}{0} \underbrace{\frac{f(x + h) - f(x)}{h}}_{\text{Difference quotient}}
|
|
\]
|
|
exists. $f'(x)$ is called the differential quotient, or derivative of $f$ in $x$. $f$ is called differentiable if it is differentiable in every $x$.
|
|
\end{defi}
|
|
|
|
\begin{eg}
|
|
\begin{enumerate}[(i)]
|
|
\item Let $f(x) = c$ with $c \in \field$ be a constant function
|
|
\[
|
|
f'(x) = \limes{h}{0} \frac{c - c}{h} = 0
|
|
\]
|
|
|
|
\item For $n \in \natn$ consider $f: \realn \rightarrow \realn ~~x \mapsto x^n$
|
|
\[
|
|
f'(x) = \limes{h}{0} \frac{(x + h)^n - x^n}{h} = \limes{h}{0} \sum_{k=0}^n \binom{n}{k}h^{k-1}x^{k-1} = nx^{n-1}
|
|
\]
|
|
|
|
\item Consider the exponential function
|
|
\[
|
|
f'(x) = \limes{h}{0} \frac{\exp(x + h) - \exp(x)}{h} = \limes{h}{0} \exp(x) \frac{\exp(h) - 1}{h} = \exp(x)
|
|
\]
|
|
\end{enumerate}
|
|
\end{eg}
|
|
|
|
\begin{thm}
|
|
Let $f: I \rightarrow \field$ be differentiable in $x$. Then $f$ is also continuous in $x$.
|
|
\end{thm}
|
|
\begin{proof}
|
|
Let $f$ be continuous in $x$. Then
|
|
\begin{equation}
|
|
\limes{h}{0} (f(x+h) - f(x)) = 0
|
|
\end{equation}
|
|
Assume $f$ to be uncontinuous in $x$. This means that
|
|
\begin{equation}
|
|
\exists \epsilon > 0 ~\forall \delta > 0 ~\exists h \in (-\delta, \delta): ~~|f(x+h) - f(x)| \ge \epsilon
|
|
\end{equation}
|
|
In particular, for every $n$ there exists an $h_n \in \left( \frac{-1}{n}, \frac{1}{n} \right) \subset \set{0}$, such that
|
|
\begin{equation}
|
|
|f(x + h_n) - f(x)| \ge \epsilon
|
|
\end{equation}
|
|
$h_n$ is a null sequence and
|
|
\begin{equation}
|
|
\left| \frac{f(x + h_n) - f(x)}{h_n} \right| \ge \frac{\epsilon}{\frac{1}{n}} = n \cdot \epsilon \longrightarrow \infty
|
|
\end{equation}
|
|
So the above term doesn't converge, thus
|
|
\begin{equation}
|
|
\frac{f(x+h) - f(x)}{h} \longrightarrow \infty
|
|
\end{equation}
|
|
Therefore, $f$ isn't differentiable in $x$.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
The inverse is not true.
|
|
\end{rem}
|
|
|
|
\begin{thm}
|
|
Let $I$ be an open interval and $f, g: I \rightarrow \field$ differentiable in $x \in I$. Then $f+g$ and $f \cdot g$ are differentiable too,
|
|
and if $g(x) \ne 0$ then $f/g$ is also differentiable.
|
|
\begin{gather*}
|
|
(f + g)'(x) = f'(x) + g'(x) \\
|
|
(f \cdot g)'(x) = f'(x)g(x) + f(x)g'(x) \\
|
|
\left(\frac{1}{g}\right)'(x) = \frac{-g'(x)}{g(x)^2}
|
|
\end{gather*}
|
|
\end{thm}
|
|
\begin{proof}
|
|
\reader
|
|
\end{proof}
|
|
|
|
\begin{thm}[Chain rule]
|
|
Let $I, J$ be open intervals, and let
|
|
\begin{align*}
|
|
g: J \longrightarrow I && f: i \longrightarrow \field
|
|
\end{align*}
|
|
$g$ and $f$ are to be differentiable in $x$ and $f(x)$ respectively. Then $f \circ g$ is differentiable in $x$ and
|
|
\[
|
|
(f \circ g)' = g'(x) \cdot f'(g(x))
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
Consider the following function
|
|
\begin{align}
|
|
\phi: J \longrightarrow \field && \phi(\xi) = \begin{cases}
|
|
\frac{f(g(x) + \xi) - f(g(x))}{\xi}, & \xi \ne 0 \\
|
|
f'(g(x)), & \xi = 0
|
|
\end{cases}
|
|
\end{align}
|
|
$\xi$ is continuous, since $f$ is continuous and
|
|
\begin{equation}
|
|
\limes{\xi}{0} \phi(\xi) = f'(g(x)) = \phi(0)
|
|
\end{equation}
|
|
$\forall \xi \in J$ the following holds
|
|
\begin{equation}
|
|
f(g(x) + \xi) - f(g(x)) = \phi(\xi) \cdot \xi
|
|
\end{equation}
|
|
With this we can now show that
|
|
\begin{equation}
|
|
\begin{split}
|
|
\frac{f(g(x+h)) - f(g(x))}{h} &= \frac{f(g(x) + (g(x + h) - g(x))) - f(g(x))}{h} \\
|
|
&= \frac{\phi(g(x + h) - g(x))(g(x + h) - g(x))}{h} \\
|
|
&= \underbrace{\phi(g(x + h) - g(x))}_{\conv{h \rightarrow 0}0} \cdot \underbrace{\frac{g(x + h) - g(x)}{h}}_{\conv{h \rightarrow 0}g'(x)} \\
|
|
&\conv{h \rightarrow 0} g'(x) \cdot f'(g(x))
|
|
\end{split}
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
\begin{defi}
|
|
Let $I$ be an interval and $f: I \rightarrow \realn$. $x_0 \in I$ is called a global maximum if
|
|
\[
|
|
f(x) \le f(x_0) ~~\forall x \in I
|
|
\]
|
|
$x_0 \in I$ is called a local maximum if
|
|
\[
|
|
\exists \epsilon > 0: ~~f(x) \le f(x_0) ~~\forall x \in (x_0 - \epsilon, x_0 + \epsilon)
|
|
\]
|
|
An extremum is either maximum or minimum.
|
|
\end{defi}
|
|
|
|
\begin{eg}
|
|
\begin{enumerate}[(i)]
|
|
\item Let $f: [-1, 1] \rightarrow \realn$, $f(x) = x^2$.
|
|
\begin{itemize}
|
|
\item $x_0 = 0$ is a local and global minimum
|
|
\item $x_0 = \pm 1$ is a local and global maximum
|
|
\end{itemize}
|
|
|
|
\item Consider
|
|
\begin{align*}
|
|
f: \realn &\longrightarrow \realn \\
|
|
x &\longmapsto \cos x + \frac{x}{2}
|
|
\end{align*}
|
|
$f$ has infinitely many local extrema, but no global ones!
|
|
|
|
\begin{center}
|
|
\begin{tikzpicture}[domain=-12:12, scale=0.3]
|
|
\draw[very thin, step=3.0, color=gray] (-11, -11) grid (11, 11);
|
|
\draw[->] (-12.2,0) -- (12.2,0) node[right] {$x$};
|
|
\draw[->] (0,-12.2) -- (0,12.2) node[above] {$y$};
|
|
\draw[smooth, thick, color=blue] plot (\x,{cos(\x r) + \x / 2}) node[right] {$f(x)$};
|
|
\end{tikzpicture}
|
|
\end{center}
|
|
|
|
\item Consider
|
|
\begin{align*}
|
|
f: \realn &\longrightarrow \realn \\
|
|
x &\longmapsto \begin{cases}
|
|
1, & x \text{ rational} \\
|
|
0, & x \text{ irrational}
|
|
\end{cases}
|
|
\end{align*}
|
|
\begin{itemize}
|
|
\item $x_0$ rational is a global maximum
|
|
\item $x_0$ irrational is a global minimum
|
|
\end{itemize}
|
|
\end{enumerate}
|
|
\end{eg}
|
|
|
|
\begin{thm}
|
|
Let $I$ be an open interval, and $f: I \realn \realn$ a function with a local extremum at $x_0 \in I$. Then
|
|
\[
|
|
f \text{ differentiable in } x_0 \implies f'(x_0) = 0
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
Assume $f'(x_0) \ne 0$ (w.l.o.g. $f'(x_0) > 0$, otherwise consider $-f$). Then
|
|
\begin{equation}
|
|
\exists \delta > 0: ~~\left| \frac{f(x_0 + h) - f(x)}{h} - f'(x_0) \right| < f'(x_0) ~~\forall h \in (-\delta, \delta)
|
|
\end{equation}
|
|
Especially
|
|
\begin{equation}
|
|
0 < \frac{f(x_0 + h) - f(x_0)}{h} ~~\forall h \in (-\delta, \delta)
|
|
\end{equation}
|
|
For $h > 0$ this means $f(x_0 + h) > f(x_0)$. And for $h < 0$ this means that $f(x_0 + h) < f(x_0)$. Thus $x_0$ is not an extremum.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
Let $f: I \rightarrow \realn$ be differentiable. To find the extrema of $f$, calculate $f'$ and find its roots.
|
|
However, the roots are to be insepcted more closely, as $f'(x_0) = 0$ is not a sufficient criterion (The function could have inflection points or behave badly at the boundaries of $I$).
|
|
\end{rem}
|
|
|
|
\begin{thm}[Mean value theorem]
|
|
Let $a, b \in \realn$ with $a < b$, and let $f, g: [a, b] \rightarrow \realn$ be differentiable. Then $\exists \xi \in (a, b)$ such that
|
|
\[
|
|
(f(b) - f(a))g'(\xi) = f'(\xi)(g(b) - g(a))
|
|
\]
|
|
|
|
\begin{center}
|
|
\begin{tikzpicture}
|
|
\begin{axis}[ytick={1, 10}, yticklabels={$f(a)$, $f(b)$}, xtick={1, 6.25, 10}, xticklabels={$a$,$\xi$,$b$}]
|
|
\addplot[thick, smooth, color=blue] coordinates {
|
|
(1, 1)
|
|
(10, 10)
|
|
} node[below right, pos=0.1] {$g(x)$};
|
|
|
|
\addplot[thick, smooth, color=red] coordinates {
|
|
(1, 1)
|
|
(2, 5)
|
|
(6, 6)
|
|
(7.8, 9.5)
|
|
(10, 10)
|
|
}node[above left, pos=0.3] {$f(x)$};
|
|
|
|
\addplot +[mark=none, dashed, gray] coordinates {(6.2, 0) (6.2, 10)};
|
|
\end{axis}
|
|
\end{tikzpicture}
|
|
\end{center}
|
|
\end{thm}
|
|
\begin{proof}
|
|
Consider all
|
|
\begin{equation}
|
|
h(x) = (f(b) - f(a))g(x) - f(x)(g(b) - f(a))
|
|
\end{equation}
|
|
$h$ is differentiable, which means $h$ is continuous on $[a, b]$:
|
|
\begin{equation}
|
|
h(a) = f(b)g(a) - f(a)g(b) = h(b)
|
|
\end{equation}
|
|
We need to show that $h'$ has a root in $[a, b]$. If $h$ is constant, this is trivial. So we assume $\exists x \in (a, b)$ such that $h(x) > h(a)$.
|
|
Since $h$ is continuous on $(a, b)$ there exists a global maximum $x_0 \in [a, b]$ with $x_0 \ne a$ and $x_0 \ne b$.
|
|
This implies that $h'(x_0) = 0$. If $h(x) < h(a)$ the same argument can be made.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
This theorem is often written as
|
|
\[
|
|
\frac{f(b) - f(a)}{g(b) - g(a)} = \frac{f'(\xi)}{g'(\xi)}
|
|
\]
|
|
And if $g(x) = x$
|
|
\[
|
|
\frac{f(b) - f(a)}{b - a} = f'(\xi)
|
|
\]
|
|
\end{rem}
|
|
|
|
\begin{cor}
|
|
Let $I$ be an open interval and $f: I \rightarrow \realn$ differentiable. Then
|
|
\begin{enumerate}[(i)]
|
|
\item $f'(I) \subset [0, \infty) \iff \text{ monotonically increasing}$
|
|
\item $f'(I) \subset (0, \infty) \implies \text{ strictly monotonically increasing}$
|
|
\item $f'(I) \subset (-\infty, 0] \iff \text{ monotonically decreasing}$
|
|
\item $f'(I) \subset (-\infty, 0) \implies \text{ striuctly monotonically decreasing}$
|
|
\end{enumerate}
|
|
\end{cor}
|
|
\begin{proof}
|
|
We will only show the "$\implies$" direction for (i). Assume $f$ isn't monotonically increasing, then $\exists x, y \in I$ such that $x < y$ but $f(x) > f(y)$.
|
|
The mean value theorem thus states, $\exists \xi \in (x, y)$ such that
|
|
\begin{equation}
|
|
f'(\xi) = \frac{f(y) - f(x)}{y- x} < 0
|
|
\end{equation}
|
|
All other statements are proven in the same fashion.
|
|
\end{proof}
|
|
|
|
\begin{eg}
|
|
$f$ strictly monotonically increasing does NOT imply that $f'(I) \subset (0, \infty)$. Consider $f(x) = x^3$.
|
|
\end{eg}
|
|
|
|
\begin{cor}[L'Hôpital's rule]
|
|
Let $a, b, x_0 \in \realn$, with $a < x_0 < b$ and let $f, g: (a, b) \rightarrow \realn$ be a differentiable function. We require $f(x_0) = g(x_0) = 0$.
|
|
If $g'(x) \ne 0 ~~\forall x \in I \setminus \set{x_0}$ and if
|
|
\[
|
|
\limes{x}{x_0} \frac{f'(x)}{g'(x)}
|
|
\]
|
|
exists, then
|
|
\[
|
|
\limes{x}{x_0} \frac{f(x)}{g(x)} = \limes{x}{x_0}\frac{f'(x)}{g'(x)}
|
|
\]
|
|
\end{cor}
|
|
\begin{proof}
|
|
Between two roots of $g$ there must be at least one root of $g'$. I.e. $g(x) \ne 0 ~~\forall x \in I \setminus \set{x_0}$.
|
|
This means, that
|
|
\begin{equation}
|
|
\forall x \in (a, x_0) ~\exists \xi_x: ~~\frac{f(x)}{g(x)} = \frac{f(x) - f(x_0)}{g(x) - g(x_0)} = \frac{f'(\xi_x)}{g'(\xi_x)} \implies \limes{x}{x_0}\frac{f'(x)}{g'(x)}
|
|
\end{equation}
|
|
Since $\xi_x \in (x, x_0)$
|
|
\begin{equation}
|
|
\xi_x \conv{x \rightarrow x_0} x_0
|
|
\end{equation}
|
|
For the limit from the left, this implies
|
|
\begin{equation}
|
|
\limes{x}{x_0} \frac{f(x)}{g(x)} = \limes{x}{x_0}\frac{f'(x)}{g'(x)}
|
|
\end{equation}
|
|
This argument can be made for the limit from the right as well.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item For the computation of the limit it is enough to consider $f$ and $g$ on $(x_0 - \delta, x_0 + \delta)$ with $\delta > 0$.
|
|
\item L'Hôpital's rule also works for one-sided limits
|
|
\item Let $f, g: (a, b) \setminus \set{x_0} \rightarrow \realn$ be differentiable. Then it is enough to require
|
|
\[
|
|
\limes{x}{x_0} f(x) = \limes{x}{x_0} g(x) = 0
|
|
\]
|
|
\item L'Hôpital's rule doesn't generally apply to complex valued functions.
|
|
\item By substituring $\tilde{f}(x) = f\left(\frac{1}{x}\right)$ and $\tilde{g}(x) = g\left(\frac{1}{x}\right)$ we can also use
|
|
\[
|
|
\limes{x}{\infty} \frac{\tilde{f}(x)}{\tilde{g}(x)} = \limes{x}{\infty} \frac{\tilde{f}'(x)}{\tilde{g}'(x)}
|
|
\]
|
|
\item The inverse
|
|
\[
|
|
L = \limes{x}{x_0} \frac{f(x)}{g(x)} \implies \limes{x}{0} \frac{f'(x)}{g'(x)} = L
|
|
\]
|
|
is NOT true.
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{eg}
|
|
Consider
|
|
\[
|
|
\limes{x}{0} \frac{x^2}{1 - \cos x} = \mathquotes{\frac{0}{0}}
|
|
\]
|
|
The functions here are
|
|
\begin{align*}
|
|
f(x) = x^2 && g(x) = 1 - \cos x
|
|
\end{align*}
|
|
with the derivatives
|
|
\begin{align*}
|
|
f'(x) = 2x && g'(x) = \sin x
|
|
\end{align*}
|
|
However, the limit of the derivatives is still
|
|
\[
|
|
\limes{x}{0} \frac{2x}{\sin x} = \mathquotes{\frac{0}{0}}
|
|
\]
|
|
We can derive the functions again
|
|
\begin{align*}
|
|
f''(x) = 2 && g''(x) = \cos x
|
|
\end{align*}
|
|
And thus
|
|
\[
|
|
\limes{x}{0} \frac{2}{\cos x} = 2 \implies \limes{x}{0} \frac{x^2}{1 - \cos x} = 2
|
|
\]
|
|
\end{eg}
|
|
|
|
\begin{thm}[Derivative of inverse functions]
|
|
Let $I$ be an open inverval, and $f: I \rightarrow \realn$ differentiable with $f'(I) \subset (0, \infty)$.
|
|
Then $f$ has a differentiable inverse function $\inv{f}(x): f(I) \rightarrow \realn$ and for $y \in f(I)$ we have
|
|
\[
|
|
\left(\inv{f}\right)'(y) = \frac{1}{f'\left(\inv{f}(y)\right)}
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
$f$ is strictly monotonically increasing, thus $\inv{f}$ exists and is continuous. Let $y \in f(I), ~x := \inv{f}(y)$ and
|
|
\begin{equation}
|
|
\xi(h) = \inv{f}(y + h) - \underbrace{\inv{f}(y)}_x
|
|
\end{equation}
|
|
Then
|
|
\begin{equation}
|
|
x + \xi(h) = \inv{f}(y + h) \implies f(x + \xi(h)) = y + h = f(x) + h
|
|
\end{equation}
|
|
Which in turn implies
|
|
\begin{equation}
|
|
f(x + \xi(h)) - f(x) = h
|
|
\end{equation}
|
|
Now we have
|
|
\begin{equation}
|
|
\begin{split}
|
|
\frac{\inv{f}(y + h) - \inv{f}(y)}{h} =& \frac{\xi(h)}{f(x + \xi(h)) - f(x)} \\
|
|
=& \inv{\left( \frac{f(x + \xi(h)) - f(x)}{\xi(h)} \right)} \\
|
|
\conv{h \rightarrow 0}& \inv{\left(f'(x)\right)} = \frac{1}{f'(\inv{f}(y))}> 0
|
|
\end{split}
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
\begin{eg}
|
|
\begin{enumerate}[(i)]
|
|
\item Let $n \in \natn$ and consider
|
|
\begin{align*}
|
|
f: (0, \infty) &\longrightarrow \realn \\
|
|
x &\longmapsto x^n
|
|
\end{align*}
|
|
The derivative is $f'(x) = nx^{n-1}$. The inverse function is
|
|
\begin{align*}
|
|
g(y) = \sqrt[n]{y} && g'(y) = \frac{1}{f'(g(y))} = \frac{1}{n\left(\sqrt[n]{y}\right)^{n-1}} = \frac{1}{n} \cdot y^{\left(\frac{1}{n} - 1\right)}
|
|
\end{align*}
|
|
|
|
\item The natural logarithm. Let $f(x) 0 \exp x$ and $g(y) = \ln y$. Then
|
|
\[
|
|
(\ln y)' = \frac{1}{\exp(\ln(y))} = \frac{1}{y}
|
|
\]
|
|
|
|
\item Let $f(x) = x^3$. Then
|
|
\[
|
|
\inv{f}(y) = \begin{cases}
|
|
\sqrt[3]{y}, & y \ge 0 \\
|
|
-\sqrt[3]{y}, & y < 0
|
|
\end{cases}
|
|
\]
|
|
$\inv{f}$ is not differentiable in $y = 0$.
|
|
\end{enumerate}
|
|
\end{eg}
|
|
|
|
\begin{defi}
|
|
Let $I$ be an open interval. $f: I \rightarrow \realn$ is said to be $(n+1)$-times differentiable if the $n$-th derivative of $f$ ($f^{(n)}$) is differentiable.
|
|
|
|
$f$ is said to be infinitely differentiable (or smooth) if $f$ is $n$ times differentiable for all $n \in \natn$.
|
|
|
|
$f$ is said to be $n$ times continuously differentiable if the $n$-th derivative $f^{(n)}$ is continuous.
|
|
\end{defi}
|
|
|
|
\begin{defi}
|
|
Let $I$ be an open interval, and $f: I \rightarrow \realn$ $n$ times differentiable in $x \in I$. Then
|
|
\[
|
|
T_n f(y) = \sum_{k=0}^n \frac{f^{(k)} (x)}{k!} (y - x)^k
|
|
\]
|
|
is called the Taylor polynomial of $n$-th degree at $x$ of $f$.
|
|
\end{defi}
|
|
|
|
\begin{thm}[Taylor's theorem]
|
|
Let $I$ be an open interval and $f: I \rightarrow \realn$ an $(n+1)$-times differentiable function.
|
|
Let $x \in I$ and $h: I \rightarrow \realn$ differentiable. For every $y \in I$, there exists a $\xi$ between $x$ and $y$ such that
|
|
\[
|
|
(f(y) - T_n f(y)) \cdot h'(\xi) = \frac{f^{(n+1)}(\xi)}{n!} (y - \xi)^n (h(y) - h(x))
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
Let
|
|
\begin{equation}
|
|
\begin{split}
|
|
g: I &\longrightarrow \realn \\
|
|
t &\longmapsto \sum_{k=0}^n \frac{f^{(k)}(t)}{k!} (y-t)^k
|
|
\end{split}
|
|
\end{equation}
|
|
Apply the mean value theorem to $g$ and $h$ to get
|
|
\begin{equation}
|
|
g'(\xi)(h(y) - h(x)) = (g(y) - g(x))h'(\xi) = (f(y) - T_nf(y))h'(\xi)
|
|
\end{equation}
|
|
and thus
|
|
\begin{equation}
|
|
\begin{split}
|
|
g'(t) &= \sum_{k=0}^n \underbrace{\left( \frac{f^{(k+1)}(t)}{k!} (y-t)^k - \frac{f^{(k)}(t)}{k!}k(y - t)^{k-1} \right)}_{\text{Telescoping series}} \\
|
|
&= \frac{f^{n+1}(t)}{n!} (y-t)^n
|
|
\end{split}
|
|
\end{equation}
|
|
By inserting $\xi$ we receive the desired equation.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item This is useful for when $h'(\xi) \ne 0$
|
|
\item The choice of $h$ can yield different errors
|
|
\[
|
|
R_{n+1}(y, x) := f(y) - T_nf(y)
|
|
\]
|
|
\item The Langrange error bound is for $h(t) = (y - t)^{n+1}$:
|
|
\[
|
|
R_{n+1}(y, x) = \frac{f^{(n+1)}(\xi)}{(n+1)!} (y-x)^{n+1}
|
|
\]
|
|
\item This theorem makes no statement about Taylor series.
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{cor}
|
|
Let $(a, b) \subset \realn$ and $f: (a, b) \rightarrow \realn$ a $n$-times continuously differentuable function with
|
|
\[
|
|
0 = f'(x) = f''(x) = \cdots = f^{(n-1)}(x)
|
|
\]
|
|
and $f^{(n)} \ne 0$. If $n$ is odd, then there is no local extremum in $x$. If $n$ is even then
|
|
\begin{align*}
|
|
f^{(n)}(x) > 0 &\implies x \text{ is a local maximum} \\
|
|
f^{(n)}(x) < 0 &\implies x \text{ is a local minimum}
|
|
\end{align*}
|
|
\end{cor}
|
|
\begin{proof}
|
|
W.l.o.g. $f^{(n)} > 0$. We will use the Taylor series with Lagrange error bound.
|
|
According to prerequisites, $f^{(n)}$ is continuous, i.e. $\exists \epsilon > 0$ such that $f^{(n)}(\xi) > 0$ on $(x - \epsilon, x + \epsilon)$.
|
|
The Taylor formula tells us, that $\forall y \in (x - \epsilon, x + \epsilon) ~\exists \xi_y \in (x - \epsilon, x + \epsilon)$ such that
|
|
\begin{equation}
|
|
f(y) - T_{n-1}(f(y)) = f(y) - f(x) = \frac{f^{(n)}(\xi_y)}{n!} (y - x)^n
|
|
\end{equation}
|
|
For $n$ odd, $f(y) - f(x)$ assumes positive and negative values in every neighbourhood of $x$. If $n$ is even then $f(y) - f(x)$ cannot be negative, thus $x$ is a local minimum.
|
|
\end{proof}
|
|
\end{document} |